2002
DOI: 10.1097/00004770-200210000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Mechanical Properties of Nickel-Titanium Endodontic Instruments

Abstract: Shape memory alloys are increasingly used in superelastic conditions under complex cyclic deformation situations. In these applications, it is very difficult to predict the service life based on the theoretical law. In the present work, fatigue properties of NiTi engine-driven rotary files have been characterized by using differential scanning calorimetry (DSC) and mechanical testing (bending). The DSC technique was used to measure precise transformation. The degree of deformation by bending was studied with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
120
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 4 publications
7
120
0
3
Order By: Relevance
“…DSC curves were very complex with irregular peaks. These results were also confirmed by other studies (28,32). Therefore, the manufacturer must perform an appropriate heat treatment, which will be accompanied by beneficial changes in mechanical properties and improved clinical performance.…”
Section: Metallurgical Characterization Of Thermomechanically-treatedsupporting
confidence: 82%
See 1 more Smart Citation
“…DSC curves were very complex with irregular peaks. These results were also confirmed by other studies (28,32). Therefore, the manufacturer must perform an appropriate heat treatment, which will be accompanied by beneficial changes in mechanical properties and improved clinical performance.…”
Section: Metallurgical Characterization Of Thermomechanically-treatedsupporting
confidence: 82%
“…At the beginning of 2000, a series of studies (27)(28)(29)(30) found that changes in the transformation behavior via heat treatment were effective in increasing the flexibility of NiTi endodontic instruments. Since then, heat-induced or heat-altering manipulations were used to influence or alter the properties of NiTi endodontic instruments, which were once cited as the main reasons for pursuing the use of NiTi instruments in endodontics.…”
Section: Metallurgical Characterization Of Thermomechanically-treatedmentioning
confidence: 99%
“…Consistent with our results, Li et al 34) suggested the fracture failure criterion to be a decrease in stiffness. On the contrary, Kuhn and Jordan 35) found that stiffness of PF instruments was increased after clinical use.…”
Section: Discussionmentioning
confidence: 94%
“…No entanto, outros estudos 25,27,42,44 demonstraram que as limas Reciproc promoveram menor remoção dentinária e mantiveram melhor a anatomia interna original do canal do que limas WaveOne.…”
Section: Discussionunclassified